1997
DOI: 10.1046/j.1471-4159.1997.69041580.x
|View full text |Cite
|
Sign up to set email alerts
|

Caffeine Stimulates Amyloid β‐Peptide Release from β‐Amyloid Precursor Protein‐Transfected HEK293 Cells

Abstract: Extracellular amyloid ß-peptide (Aß) deposition is a pathological feature of Alzheimer's disease and the aging brain. Intracellular Aß accumulation is observed in the human muscle disease, inclusion body myositis. Aß has been reported to be toxic to neurons through disruption of normal calcium homeostasis. The pathogenic role of Aß in inclusion body myositis is not as clear. Elevation of intracellular calcium following application of calcium ionophore increases the generation of Aß from its precursor protein (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
54
0
4

Year Published

2000
2000
2016
2016

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 77 publications
(62 citation statements)
references
References 80 publications
4
54
0
4
Order By: Relevance
“…Studies to date have demonstrated conflicting results. In non-excitable cells, pharmacological elevation of [Ca ϩ2 ] i has been shown to both increase and decrease A␤ levels (43)(44)(45). In neurons, the data on the relationship between Ca 2ϩ influx and A␤ production is equally unclear.…”
Section: Discussionmentioning
confidence: 99%
“…Studies to date have demonstrated conflicting results. In non-excitable cells, pharmacological elevation of [Ca ϩ2 ] i has been shown to both increase and decrease A␤ levels (43)(44)(45). In neurons, the data on the relationship between Ca 2ϩ influx and A␤ production is equally unclear.…”
Section: Discussionmentioning
confidence: 99%
“…Since the large hydrophilic loop regions are divergent between PS1 and PS2 and no FAD mutation has been identified in the putative sorcin binding region of PS2 (synexin homologous domain), the exact contributions of sorcin and other PS1/PS2 loop-interacting molecules to AD neuropathogenesis have not been fully elucidated (16 -19, 58). Interestingly, increased amyloid ␤-peptide levels can result from RyR-driven elevations in intracellular Ca 2ϩ (59). On the other hand, decreased RyR activity correlates with early pathological changes in AD (60).…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, by impairing coupling of muscarinic acetylcholine receptors to Gq11 via a membrane lipid peroxidation-mediated mechanism, A␤ can suppress Ca 2ϩ responses to acetylcholine (Kelly et al, 1996). In a cyclical fashion, it has also been shown that Ca 2ϩ can initiate and accelerate the formation of pathogenic A␤ species (Isaacs et al, 2006), but relevant to this topic is that Ca 2ϩ from RyR-sensitive stores in particular can enhance the production and release of A␤ peptides (Querfurth and Selkoe, 1994;Querfurth et al, 1997) (Fig. 4).…”
Section: E Alzheimer Diseasementioning
confidence: 99%